Isolation and molecular identification of Nipah virus from pigs - Abu Bakar, Sazaly; Li, Yen Chang; A. R., Mohd Ali; Syed Hassan, Sharifah; Yusoff, Khatijah; Zamrod, Zulkeflie (Centers for Disease Control and Prevention, 2004)
Nipah viruses from pigs from a Malaysian 1998 out-break were isolated and sequenced. At least two different Nipah virus strains, including a previously unreported strain, were identified. The findings highlight the possibility that the Malaysia outbreaks had two origins of Nipah virus infections.